Unveiling ChatGPT in tourism education: exploring perceptions, advantages and recommendations from educators - Altun, Ozlem; Saydam, Mehmet Bahri; Karatepe, Tuna; Dima, Stefana Maria (Emerald Group Publishing Ltd, 2024)
PurposeFollowing the remarkable debut of ChatGPT and its rapid adoption by a global audience since its launch in November 2022, this study delves into educators' perceptions of ChatGPT within the specialized domains of tourism and hospitality education. While acknowledging ChatGPT's swift rise and advanced capabilities, this research aims to comprehensively explore educators' perspectives, advantages and concerns regarding its integration into academic settings.Design/methodology/approachA qualitative approach was utilized to reveal dominant themes from in-depth, semi-structured face-to-face interviews with twenty lecturers in tourism faculties in North Cyprus. Collected responses from respondents were subjected to analysis using Leximancer software.FindingsOur analysis unearthed seven significant themes encapsulating educators' perceptions of ChatGPT: 1 - reliability and accuracy concerns; 2 - dependency; 3 - student engagement; 4 - ethical considerations; 5 - time efficiency and productivity; 6 - teacher-student interaction and 7 - learning flexibility. Noteworthy positive perceptions emerged regarding student engagement, time efficiency and productivity, and learning flexibility.Originality/valueThis study contributes to the originality of research by addressing the underexplored aspect of educators' perceptions of ChatGPT within the domains of tourism and hospitality education, shedding light on its potential implications, advantages and drawbacks in a specialized educational context. Furthermore, it aims to offer insights into educators' recommendations for the effective incorporation of ChatGPT technologies into this specific educational setting, filling a crucial gap in understanding the integration of artificial intelligence (AI) in specialized fields of study.
Keywords: Tourism education; Artificial intelligence; ChatGPT; Lecturers; Sustainability